Malang Raya Sebagai Locus Theologicus: Upaya mendalami isu-isu menonjol dalam masyarakat setempat - Maro, Kornelius; Junianto, Bernadus; Poso, Kristianus; Mandut, Saverinus; Asmat, Tarsisius; Snae, Yeremias Benediktus Sae (Perspektif, 2016)
Malang is such a unique place in Indonesia with its long appealing history and great personages who have had an extensive influence not only for the region but also for the country. Nowdays it attracts people from the whole country as well as foreigners to come and sojourn in Malang Raya (Greater Malang), either for commerce, education, or tourism. The research on the three Radars of Malang, Batu, and Kanjuruhan of the Jawa Pos daily newspaper during the month of August and September 2015 reveals the ‘Spirit of Malang’. The research group also found out that there were (are) serious issues accompany the deve-lopment of modern Malang Raya. The findings challenge the Church to respond them critically as well as Christiantly.